Islamic thought in the Middle Ages : studies in text, transmission and translation, in honour of Hans Daiber - Akasoy, Anna.; Daiber, Hans, 1942-; Raven, Wim. (Islamic Philosophy, Theology and Science. Texts and Studies, 2008)
The history of Islamic thought in the Middle Ages, the impact of Greek philosophy and science, and the formation of an own theological tradition, is a long and complex one. The articles in this volume dedicated to Hans Daiber, one of the pioneering scholars in this field, offer new insights from a variety of perspectives: philological, philosophical, and historical. The subjects range from Islamic philosophy and theology, over the history of science, the transmission into other medieval cultures to language and literature. In addition to their specific discoveries, they give an impression of the dynamics of medieval Islamic intellectual history as well as of the diversity of approaches needed to understand this dynamics.